Atom Tunneling in Chemistry. Issue 18 (16th March 2016) - Meisner, Jan; Kästner, Johannes
Abstract: Quantum mechanical tunneling of atoms is increasingly found to play an important role in many chemical transformations. Experimentally, atom tunneling can be indirectly detected by temperature‐independent rate constants at low temperature or by enhanced kinetic isotope effects. In contrast, the influence of tunneling on the reaction rates can be monitored directly through computational investigations. The tunnel effect, for example, changes reaction paths and branching ratios, enables chemical reactions in an astrochemical environment that would be impossible by thermal transition, and influences biochemical processes. Abstract : Tunnel vision : The quantum mechanical tunnel effect is increasingly found to influence many chemical reactions. Although it can only be detected indirectly in experiments, computational investigations allow direct observation. Here, we highlight cases in which the tunnel effect changes reaction paths and branching ratios, enables chemical reactions in an astrochemical environment, and influences biochemical processes.